Hybrid Hydrogel Composed of Polymeric Nanocapsules Co-Loading Lidocaine and Prilocaine for Topical Intraoral Anesthesia - Muniz, Bruno Vilela; Baratelli, Diego [UNESP]; Di Carla, Stephany; Serpe, Luciano; da Silva, Camila Batista; Guilherme, Viviane Aparecida; Ribeiro, Lígia Nunes de Morais; Cereda, Cintia Maria Saia; de Paula, Eneida; Volpato, Maria Cristina; Groppo, Francisco Carlos; Fraceto, Leonardo Fernandes [UNESP]; et al. (Springer Nature, 2018)
This study reports the development of nanostructured hydrogels for the sustained release of the eutectic mixture of lidocaine and prilocaine (both at 2.5%) for intraoral topical use. The local anesthetics, free or encapsulated in poly(ε-caprolactone) nanocapsules, were incorporated into CARBOPOL hydrogel. The nanoparticle suspensions were characterized in vitro in terms of particle size, polydispersity, and surface charge, using dynamic light scattering measurements. The nanoparticle concentrations were determined by nanoparticle tracking analysis. Evaluation was made of physicochemical stability, structural features, encapsulation efficiency, and in vitro release kinetics. The CARBOPOL hydrogels were submitted to rheological, accelerated stability, and in vitro release tests, as well as determination of mechanical and mucoadhesive properties, in vitro cytotoxicity towards FGH and HaCaT cells, and in vitro permeation across buccal and palatal mucosa. Anesthetic efficacy was evaluated using Wistar rats. Nanocapsules were successfully developed that presented desirable physicochemical properties and a sustained release profile. The hydrogel formulations were stable for up to 6 months under critical conditions and exhibited non-Newtonian pseudoplastic flows, satisfactory mucoadhesive strength, non-cytotoxicity, and slow permeation across oral mucosa. In vivo assays revealed higher anesthetic efficacy in tail-flick tests, compared to a commercially available product. In conclusion, the proposed hydrogel has potential for provision of effective and longer-lasting superficial anesthesia at oral mucosa during medical and dental procedures. These results open perspectives for future clinical trials.